What Homoeopaths Need to know about Clinical Establishments Act? - An Overview (Homoeopathy for All, 2021)
A homoeopath has education and training of five and a half years to expertise himself to be qualified to treat patients. At the end of the course, he is certified for the same. With this certificate, he can register himself in the state or central council and can set up a clinic for the practice anywhere in the country. To start a clinic a homoeopath just needs a valid degree and registration with the state board of Homoeopathy. Registration number with the Central Council of Homoeopathy is needed if you wish to practice in the other state instead of where you got your degree from. Further, as per Clinical Establishments Act 2010, all clinics and hospitals in the country need to be registered with the concerned authority. So a homoeopath when starts his clinic, simultaneously needs to get registered under the Clinic Establishments Act with the concerned District Authority as well. Many homoeopaths do not know much about this act. Hence this article focusses on the act and other details required for the homoeopaths to register their clinics and hospitals.
Keywords: Clinical Establishments Act 2010; homoeopaths